Design, construction and 13 K conduction-cooled operation of a 3 T 100 mm stainless steel cladding all-REBCO magnet. (12th September 2017) - Jang, Jae Young; Yoon, Sangwon; Hahn, Seungyong; Hwang, Young Jin; Kim, Jaemin; Shin, Kang Hwan; Cheon, Kyekun; Kim, Kwanglok; In, Sehwan; Hong, Yong-Ju; Yeom, Hankil; Lee, Hunju; et al.
Abstract: A conduction-cooled 3 T 100 mm winding bore multi-width and no-insulation (NI) all-REBCO magnet was designed, constructed and tested at 13 K. The magnet consists of a stack of double pancake (DP) coils wound with, for the first time, REBCO tapes having a 1 μ m thick layer of stainless steel, named 'metallic cladding', that surrounds the tapes in a hermetic way to substantially reduce the NI charging delay. After construction, the magnet was cooled down to the target operating temperature of 13 K using a two-stage pulse-tube cryo-cooler. During charging–discharging tests up to 200 A, magnetic center field, voltage of each DP coil, power supply current, and magnet temperature were monitored. The charging time constant of the magnet was measured to be about 10.1 s, 13 times smaller than that of its NI counterpart. The magnet experienced, due to an unexpected power supply trip, a sudden discharge at a peak coil current density of 353 A mm 2, yet it survived without any degradation. The results demonstrated strong potential of the metallic cladding NI-REBCO magnet for significant charging-delay reduction and self-protecting operation.